The aphrodisiac herb Carpolobia: A biopharmacological and phytochemical review - Nwidu, Lucky Lebgosi; Nwafor, Paul Alozie; Vilegas, Wagner [UNESP] (Manuscript Technomedia LLP, 2015)
Any agent with the ability to provoke sexual desire in an individual is referred to as an aphrodisiac. Aphrodisiac plants are used in the management of erectile dysfunction (ED) in men. One such plant popular in West and Central Africa among the Pygmies of Cameroon, Ipassa of Garbon, and the Yoruba, Ibo, Efik and Ijaw peoples of Nigeria is Carpolobia. It is an accepted and commonly utilized herbal booster of libido. It is used to cure male infertility and to boosts libido thereby augmenting male sexual functions or it is used to induce penile erection, and enhance male virility. The chewing stick prepared from the stem and root of either Carpolobia alba (CA) or Carpolobia lutea (CL) is patronized because it boosts male sexual performance. The genus Carpolobia has over 14 species. The leaf essential oil contains a variety of terpenoids, while polyphenols and triterpenoid saponins have been isolated from the root and leaf extracts respectively. Other ethnomedicinal uses include curing of stomach ailments, rheumatism, fever, pains, insanity, dermal infection, venereal diseases; to promote child birth; and as a taeniafuge and vermifuge. In spite of its popularity, no scientific data reviewing the biopharmacological and phytochemical activities of Carpolobia exist to our knowledge. The aim of this work is to collate all available published scientific reports in the literature on Carpolobia in a review paper. In this review, an overview of the morphology, taxonomy, ethnomedicinal claims, geographical distribution, and structurally elucidated compounds that are secondary metabolites isolated and characterized from Carpolobia species is established. The pharmacological assays, phytochemical screenings, and toxicological reports are also reviewed.
Keywords: Carpolobia; Carpolobia alba; Carpolobia lutea; ethnopharmacology; phytochemistry